2013
DOI: 10.1128/jcm.01627-12
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a New Clinical Yeast Species, Candida tunisiensis sp. nov., Isolated from a Strain Collection from Tunisian Hospitals

Abstract: dFrom a collection of yeast isolates isolated from patients in Tunisian hospitals between September 2006 and July 2010, the yeast strain JEY63 (CBS 12513), isolated from a 50-year-old male that suffered from oral thrush, could not be identified to the species level using conventional methods used in clinical laboratories. These methods include matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS), germ tube formation, and the use of CHROMagar Candida and metabolic gallerie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…As observed by others and in our study many new types of yeast are reported as probable human pathogens which should be included in diagnostic protocols. 54 In the present study, a total of six species viz., Cy. fabianii, T. asahii, C. africana, K. marxianus, Lodderomyces sp., Ko.…”
Section: Diversity Of Clinical Yeast Isolatesmentioning
confidence: 94%
“…As observed by others and in our study many new types of yeast are reported as probable human pathogens which should be included in diagnostic protocols. 54 In the present study, a total of six species viz., Cy. fabianii, T. asahii, C. africana, K. marxianus, Lodderomyces sp., Ko.…”
Section: Diversity Of Clinical Yeast Isolatesmentioning
confidence: 94%
“…In recent years, methods for the rapid identification of microorganisms have been developed, which have enabled the detection of new species and characterization of their components and/or metabolites. These methods have been based on proteomic profiles, using MALDI-TOF MS, and metabolome profiles, by 1 H-NMR and hyphenated mass spectrometry 8 , 12 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Different Candida species may have very different antifungal susceptibility profiles. In this context, it is important to obtain accurate taxonomic identification to apply appropriate treatments 8 , 9 . Traditionally, fungi are identified by phenotypic traits including morphology, colony appearance and pigmentation in chromogenic culture medium 8 , 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations